A post-marketing survey evaluating the safety and efficacy of a fixed-dose single-pill combination of cilnidipine and valsartan in patients with hypertension: Real-world JSH 2014 and 2019 implementations. (17th August 2020) - Matsuda, Saori; Nagahama, Shinobu; Kurose, Yoshiki; Wakabayashi, Maki; Sugii, Hitoshi; Teshima, Tsukasa; Suzuki, Noriyuki; Kario, Kazuomi
ABSTRACT: Methods: : The home blood pressure control by a single-pill combination of cilnidipine and valsartan (HOPE-Combi) survey sought to evaluate the safety and efficacy of cilnidipine 10 mg/valsartan 80 mg single-pill combination (SPC of Cil/Val) treatment in patients with hypertension for over 12 months. Of 2622 subjects' data; we analyzed 2572 cases for safety and 2372 cases for efficacy. Results: Adverse drug reaction (ADR) incidence rate was 3.77% (97 of 2572 patients). The frequency of ADRs did not differ between patients aged <75 years and those aged ≥75 years (3.70% vs. 3.93%, respectively); between patients with and without chronic liver disease (CLD; 6.44% vs. 3.54%, respectively); and between patients with and without chronic kidney disease (CKD; 5.26% vs. 3.59%, respectively). Office systolic blood pressure (BP) was reduced from 149.5 ± 19.6 mmHg to 133.5 ± 14.8 mmHg (−15.8 mmHg, P < .01); pulse rate was also reduced 75.5 ± 12.2 bpm to 73.5 ± 11.3 bpm (−1.8 bpm, P < .01) after 12 months. Conclusions: : The SPC of Cil/Val was safe and effective in treating BP of hypertensive patients in real-world settings.